Laughter on Social Media Twitter: The Influence of Different Types of Humor on Positive Emotions in Generation Z - Suhariningsih, Utami; Nurhayati, Siti Rohmah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
This study aimed to investigate the impact of humour types on positive emotions of Generation Z social media users on Twitter. An experimental method was adopted, with a one-shot case study design under a pre-experimental framework. The participants were 211 individuals divided into 4 groups of different types of humour, namely sarcasm text, entertainment text, sarcasm meme, and entertainment meme. The post hoc test results showed that different types of humour had varying effects on enhancing positive emotions among Generation Z users on Twitter. Sarcasm text had the most significant impact, achieving the highest average value of 68.77, while entertainment meme featured the least influence, with the lowest average value of 59.66. The ANOVA test further confirmed these variations, with an F-test significance value of 0.000 (p < 0.05).